Assessing the Structural Reform of National Accreditation Bodies and Its Implications for Education Quality Control in Indonesia - Utari, Tria Ina; Bafadal, Ibrahim; Ubaidillah, Aan Fardani (Mimbar Sekolah Dasar, 2025)
Changes in the scope of educational organizations are believed to ensure that all levels of education in Indonesia receive accreditation in accordance with the National Education Standards. This study aims to examine the impact of the structural transition from National Accreditation Board for Schools and Madrasahs to National Accreditation Board for Early Childhood Education, Primary Education, and Secondary Education in implementing quality assurance in Indonesian education. A literature review approach is employed in this research. The findings indicate that changes in name and accreditation scope have led to structural and functional transformations within the National Accreditation Body. The functions of National Accreditation Board for Early Childhood Education, Primary Education, and Secondary Education are expected to accommodate more accurate and beneficial educational services tailored to each level, including early childhood education, primary education, and secondary education. The implications of this transition are believed to enhance the quality of Indonesia’s accreditation institutions by fostering greater transparency and openness in carrying out their duties and functions as quality assurance bodies in the country.